Program Turikale terhadap Perubahan Saturasi Oksigen dan Kecemasan dalam Menghadapi Masa Pandemi COVID-19 - Rosita Passe; Aminuddin Aminuddin; Ayu Lestari; Jumrah Sudirman (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the effect of physical exercise on oxygen saturation and anxiety in dealing with the COVID-19 pandemic in the Timbuseng Village community, Takalar Regency. The research design was quasi-experimental with a pretest-posttest design with a control group. The results showed that oxygen saturation with physical activity where p-value = 0.000 <0.05 and anxiety about physical activity where p-value = 0.000 <0.05. In conclusion, there is a significant effect of giving physical exercise intervention on the value of oxygen saturation and anxiety in the Timbuseng village community, Takalar district. Keywords: Anxiety, Physical Exercise, Oxygen Saturation